Arte e Matemática no traço de Lothar Charoux - Jelin, D. Fernandes; Venezuela, A. L. (Trends in Computational and Applied Mathematics, 2024)
<span class="_base_158wm_54" data-slate-leaf="true" data-slate-fragment="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">This study takes a mathematical look at a work of art by one of the pioneers of Brazilian concretism, Lothar Charoux (1912-1987). We examined a drawing with a striking geometric appeal dating back to 1958. Based on its patterns, we defined a set of differentiable parameterized curves, referred to as ``hidden Charoux spirals'', and studied their curvature. We intend that the mathematical description of this artwork, using the tools of differential geometry, can enrich the artist's critical fortune. To this end, we confronted the mathematical description of the drawing with the impressions Charoux left among critics, cultural journalists, and art historians.